Correlation between work engagement and quality of life of users living with support in residential units - Stanojkovska-Trajkovska, Natasha; Georgievska, Sofija; Arnаudovska, Maja (Ревија за социјална политика/Journal of Social Policy, 2019)
Over the past five decades, a number of changes have occurred in the treatment of people with intellectual disabilities. There is a tendency to redesign the society mainly intended for „healthy, capable and powerful“ and to create an inclusive society with equal access to all its citizens. Deinstitutionalization is one of the processes that particularly contributed to improving the quality of life of adults with intellectual disabilities and their social inclusion in all mainstreams of contemporary living. Assessing the quality of life and work engagement of adult users is inevitable, as the process results in new configurations of needs and services for more successful and better inclusion in society. The survey includes 80 persons with intellectual disability, beneficiaries of residential units with supported living in Skopje and Negotino. The common findings suggest that users of these housing units consider that additional activities are required to organize their spare time. It is also necessary to engage users with more activities as it affects their mood and are considered socially useful citizens. Generally, it can be concluded that work engagement affects the quality of life of this category of peoples, indicating the need to expand the activity of day care centres in Skopje and Negotino and acceptance in the local environment for this category of people. This will contribute to greater independence and social inclusion of adults with intellectual disabilities.
Keywords: intellectual disability; moderate and severe intellectual disability; home engagement and gardening; engagement in day-care centre; engagement in community